“I just had the feeling that the interval training is more beneficial”: young adults' subjective experiences of physical fitness and the role of training modes - Gropper, Hannes; John, Jannika M.; Sudeck, Gorden; Thiel, Ansgar (Frontiers in Sports and Active Living, 2023)
Objective Compelling evidence has shown that high-intensity interval training (HIIT) is associated with substantial increases in physical fitness. However, little is known about whether and how individuals experience these adaptations over time. The purpose of this study is, therefore, to explore how physically inactive young adults subjectively experience physical fitness and its development as they start to exercise and how these experiences relate to different intensity domains (i.e., moderate and severe) as well as to training modes [i.e., HIIT and moderate intensity continuous training (MICT)] and their sequential administration (i.e., HIIT–MICT and MICT–HIIT). Methods Thirty-one inactive participants completed a 15-week two-period sequential exercise intervention in which they first trained for six weeks in a HIIT or a MICT group and subsequently switched training modes. Interviews using the biographical mapping method were conducted at the end of the intervention to assess participants’ exercise- and fitness-related experiences over the past weeks. To assess experiential patterns, we conducted a reflexive thematic analysis. Results We developed three themes that represent the temporal and processual character of starting to exercise after a prolonged period of inactivity: (1) Inactive young adults are not all the same when starting to exercise; (2) Developing physical fitness is a multi-faceted and individual experience; and (3) Feeling physically fit (or not) fosters large-scale effects. Conclusion Our results show that, in retrospect, participants mostly deemed HIIT to be more effective than MICT. Our findings also emphasize that physical fitness is a complex and subjective experience that manifests in various ways over time. The idiosyncrasy of physical fitness experiences reiterates the necessity for individually tailored exercise prescriptions instead of one-size-fits-all approaches.